2017
DOI: 10.1038/srep41008
|View full text |Cite
|
Sign up to set email alerts
|

The systematic analysis of coding and long non-coding RNAs in the sub-chronic and chronic stages of spinal cord injury

Abstract: Spinal cord injury (SCI) remains one of the most debilitating neurological disorders and the majority of SCI patients are in the chronic phase. Previous studies of SCI have usually focused on few genes and pathways at a time. In particular, the biological roles of long non-coding RNAs (lncRNAs) have never been characterized in SCI. Our study is the first to comprehensively investigate alterations in the expression of both coding and long non-coding genes in the sub-chronic and chronic stages of SCI using RNA-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 71 publications
0
66
0
Order By: Relevance
“…For example, it has been shown that lncRNA UCA1 can regulate neural stem cell differentiation by regulating miR‐1/Hes1 expression (Zheng et al, ). As well known, SCI is one of the most debilitating neurological diseases and most of SCI patients remain in the chronic phase (Duran et al, ). XIST contributes to the pathogenesis of SCI by sponging miR‐494 and regulating PTEN/AKT signaling axis and it is suggested that XIST can serve as a promising molecular target for treating SCI (Gu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that lncRNA UCA1 can regulate neural stem cell differentiation by regulating miR‐1/Hes1 expression (Zheng et al, ). As well known, SCI is one of the most debilitating neurological diseases and most of SCI patients remain in the chronic phase (Duran et al, ). XIST contributes to the pathogenesis of SCI by sponging miR‐494 and regulating PTEN/AKT signaling axis and it is suggested that XIST can serve as a promising molecular target for treating SCI (Gu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Adapted from Duran et al . with modifications and permission. ( B ) Left panel: Browser view depicting the gene expression of DE lnc RNA LOC 100912503 and its closest DE protein‐coding gene Bmpr1a at different time points of the subchronic and chronic stages of rat SCI .…”
Section: Functions Of Lncrnas In Acute and Chronic Cns Injuriesmentioning
confidence: 99%
“…LncRNAs are in blue and proteincoding genes are in red colour. Adapted from Duran et al[24] with permission and modifications.…”
mentioning
confidence: 99%
“…These results suggested that lncRNA expression was highly dynamic across different stages. Nonetheless, these studies have aimed to reveal the lncRNA profiles in different post‐injury time‐points, from immediate, acute, subchronic to chronic phases after SCI (Figure ). These studies provided preliminary views on stage‐specific lncRNA modulation.…”
Section: Lncrna Expression Profiling In Scimentioning
confidence: 99%